The immunoglobulin of yolk and cerium oxide-based fibrous poly(L-lactide-co-glycolide)/gelatin dressings enable skin regeneration in an infectious wound model - Xinyuan Zhao; Changwen Weng; Hao Feng; Muhammad Shafiq; Xinyi Wang; Lei Liu; Lu Han; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Zhengchao Yuan; Xiumei Mo; Yanbiao Wang (Materials Today Bio)
The bacterial infection and oxidative wound microenvironment delay skin repair and necessitate intelligent wound dressings to enable scarless wound healing. The immunoglobulin of yolk (IgY) exhibits immunotherapeutic potential for the potential treatment of antimicrobial-resistant pathogens, while cerium oxide nanoparticles (CeO2 NPs) could scavenge superoxide dismutase (SOD) and inflammation. The overarching objective of this study was to incorporate IgY and CeO2 NPs into poly(L-lactide-co-glycolide)/gelatin (PLGA/Gel)-based dressings (P/G@IYCe) for infected skin repair. The P/G@IYCe manifested good biocompatibility as well as showed significant antibacterial effect against Staphylococcus aureus (S. aureus) and Escherichia coli (E.coil) in vitro. Subcutaneous implantation of membranes in rats exhibited cytocompatibility. Transplantation of membranes in S. aureus-infected full-thickness excisional defects manifested significant beneficial effect of P/G@IYCe dressings than that of the other groups in terms of the scar tissue formation, inflammation resolution, and scavenging of reactive oxygen species (ROS) at 2 weeks post-transplantation. Taken together, the dual delivery of IgY and CeO2 may enable intelligent wound dressings.